Ammonia tolerance of Litopenaeus vannamei (Boone) larvae. Issue 3 (12th September 2012) - de, María; Sonnenholzner, Stanislaus; Wille, Mathieu; Sorgeloos, Patrick
Abstract The tolerance of Litopenaeus vannamei larvae to increasing concentrations of total ammonia nitrogen (TAN) using a short‐term static renewal method at 26°C, 34 g L−1 salinity and pH 8.5 was assessed. The median lethal concentration (24 h LC50) for TAN in zoea (1‐2‐3), mysis (1‐2‐3) and postlarvae 1 were, respectively, 4.2‐9.9‐16.0; 19.0‐17.3‐17.5 and 13.2 mg L−1TAN (0.6‐1.5‐2.4; 2.8‐2.5‐2.6 and 1.9 mg L−1 NH3‐N). The LC50 values obtained in this study suggest that zoeal and post‐larval stages are more sensitive to 24 h ammonia exposure than the mysis stage of L. vannamei larvae. On the basis of the ammonia toxicity level (24 h LC50) at zoea 1, we recommend that this level does not exceed 0.42 mg L−1 TAN – equivalent to 0.06 mg L−1 NH3‐N – to reduce ammonia toxicity during the rearing of L. vannamei larvae.